Ruthenium(II) Complexes as Potential Apoptosis Inducers in Chemotherapy - Zheng, Kangdi; Wu, Qiong; Wang, Chengxi; Tan, Weijun; Mei, Wenjie (Anti-Cancer Agents in Medicinal Chemistry, 2017)
Herein, the development of ruthenium complexes as potential apoptosis inducers, as well as their underlying mechanism has been reviewed. In recent years, various ruthenium complexes have been designed and their in vitro and in vivo inhibitory activities against various types of tumor cells have been evaluated extensively. It’s demonstrated that ruthenium complexes can induce apoptosis of tumor cells through the signal pathway of mitochondria-mediated, death receptor-mediated, and/or endoplasmic reticulum (ER) stress pathways. Alternately, the binding behavior of these ruthenium(II) complexes with DNA, especially with Gquadruplex DNA may play a key role in the DNA damage of tumor cells, and thus provides a versatile tool to rational design novel ruthenium complexes with high activity and selectivity.
Keywords: G-quadruplex